Brentton Woods At Forty. (Pamphlet Series; Pamphlet Series, No., 1995)
This chapter presents several papers included in the Bretton Woods conference. The Bretton Woods Conference of 1944 had left many issues of development finance unresolved. In fact, very early, the World Bank took a different direction from that envisaged by its founders. The IMF came into existence on December 27, 1945. The eventual growth in the Fund's activities led to the disappearance of the nonresident Executive Director. A teleological approach in the examination of the IMF's authority was inspired not only by the principle that the Fund must be effective in the pursuit of its purposes but also by the belief that the Articles, and especially the provisions on the par value system, constituted an international monetary system. In the 1950s, the Bank made an important contribution to helping countries cope with the external debt problems left over from the 1930s. Moreover now it is trying, in cooperation with the IMF, to help countries make necessary adjustments on a case-by-case basis.